New Volume-Stable Collagen Matrix and Modified Coronally Advanced Flap to Treat Multiple Gingival Recessions Associated with Partially Restored Non-Carious Cervical Lesions: A Case Report - Santamaria, Mauro Pedrine [UNESP]; Miguel, Manuela Maria Viana [UNESP]; Rossato, Amanda [UNESP]; Bonafe, Ana Carolina Ferreira [UNESP]; Ferraz, Lais Fernanda Ferreira [UNESP]; Santos, Lucio Murilo dos [UNESP]; Mathias-Santamaria, Ingrid Fernandes [UNESP] (Wiley-Blackwell, 2020)
Introduction: Gingival recession (GR) is a prevalent problem that is related to esthetic demands and dentin hypersensitivity. Frequently, GR is associated with non-carious cervical lesion (NCCLs) forming a combined defect (CD), which requires restorative and surgical treatment. Connective tissue graft procedures allow predictable root coverage but can result in patient discomfort. Case Presentation: This first case report describes multiple GRs associated with B+ NCCL at teeth #4 and #6 of a 27-year-old patient with a thin periodontal phenotype. The aim of this report was to evaluate the 6-month outcome of a new volume-stable collagen matrix (VCMX) combined with modified coronally advanced flap (MCAF) and partial restoration to treat CDs. After 6 months, significant improvement was observed regarding CD coverage (69.05%), recession reduction (2.25 mm), gingival thickness gain (0.74 mm), and keratinized tissue width gain (0.75 mm). In addition, excellent esthetic evaluation and patient comfort were achieved by using the biomaterial. Conclusion: VCMX associated with MCAF and partial restoration may be an option to treat multiple recession defects plus B+ NCCLs.
Keywords: Biocompatible materials; dental; esthetics; gingival recession; tooth abrasion